Organ-on-a-Chip: Opportunities for Assessing the Toxicity of Particulate Matter - Yang, Jia-Wei (Front Bioeng Biotechnol, 2020)
Recent developments in epidemiology have confirmed that airborne particulates are directly associated with respiratory pathology and mortality. Although clinical studies have yielded evidence of the effects of many types of fine particulates on human health, it still does not have a complete understanding of how physiological reactions are caused nor to the changes and damages associated with cellular and molecular mechanisms. Currently, most health assessment studies of particulate matter (PM) are conducted through cell culture or animal experiments. The results of such experiments often do not correlate with clinical findings or actual human reactions, and they also cause difficulty when investigating the causes of air pollution and associated human health hazards, the analysis of biomarkers, and the development of future pollution control strategies. Microfluidic-based cell culture technology has considerable potential to expand the capabilities of conventional cell culture by providing high-precision measurement, considerably increasing the potential for the parallelization of cellular assays, ensuring inexpensive automation, and improving the response of the overall cell culture in a more physiologically relevant context. This review paper focuses on integrating the important respiratory health problems caused by air pollution today, as well as the development and application of biomimetic organ-on-a-chip technology. This more precise experimental model is expected to accelerate studies elucidating the effect of PM on the human body and to reveal new opportunities for breakthroughs in disease research and drug development.